A new concept of stabilization policy - Manfred Willms (Intereconomics, 1972)
Inflation is the most important economic problem in Germany today. Although the economy is still in a process of slow recovery and there are still excess capacities, inflation continues. Consumer prices increase at an annual rate close to 6 p.c. and the GNP deflator is close to 8 p.c. Economists and politicians are looking for a new concept of stabilization policy.
Keywords: 330; Economic Policy